487. THE OUTCOME OF NIVOLUMAB THERAPY FOR PLATINUM-RESISTANT UNRESECTABLE ADVANCED OR RECURRENT ESOPHAGEAL CANCER. (24th September 2022) - Kanamori, Kohei; Tajima, Kohei; Yatabe, Kentaro; Shoji, Yoshiaki; Yamamoto, Miho; Kazuno, Akihito; Koyanagi, Kazuo
Abstract: In a phase III study, nivolumab treatment significantly prolonged survival compared with taxanes in patients with unresectable advanced or recurrent esophageal cancer who had become intolerant to first-line chemotherapy with 5-FU and platinum-based agents. We will report our experience and results of treatment with nivolumab at our hospital. The subjects were 46 patients treated with nivolumab for unresectable advanced or recurrent esophageal cancer at our hospital from January 2019 to December 2021. Clinical factors and treatment effects were investigated. The initial response was PR in 12 cases, SD in 18 cases, PD in 12 cases, and unevaluable in 4 cases. Median duration of nivolumab treatment was 3 months (1-18 months). Adverse effects grade 3 were found in 9 cases and grade 2 in 9 cases. Nivolumab was discontinued in 5 cases (10.8%) due to adverse effects. Compared between cases who discontinued nivolumab within 2 months due to ineffectiveness or adverse effects and those who were able to continue for more than 2 months, overall survival was significantly prolonged in the latter group (median OS: 23.8 vs. 36.8 months, p=0.05). In patients with unresectable advanced or recurrent esophageal cancer who responded to nivolumab, it was suggested that the drug may improve prognosis. The incidence of unsustainable adverse effects is relatively high, and it is important to control adverse effects.